Thermal and UV curable adhesive compositions
By using heat and UV-curable adhesive compositions, the problem of adhesives easily peeling off during heat curing in compact camera module assembly is solved, achieving more stable adhesion and improving heat resistance after curing.
Patent Information
- Application Number
- CN202080079193.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-15
- Filing Date
- 2020-11-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-11-13
AI Technical Summary
When assembling the compact camera module, the thermally cured adhesive causes a change in the distance between the lens and the image sensor, and the adhesive of the high thermal expansion coefficient material is prone to peel off during thermal curing and loses heat resistance.
A heat and UV curing adhesive composition contains polyurethane acrylic hypocatty, acrylic mono, particle rubber, polyamine curing agent and optical polymerous causes with peridamine and/or amine. The molecular weight is 4,000 or higher, and the particle rubber content is 5 % or more.
Reduces adhesive peeling during thermal curing, improves heat resistance after curing, and ensures stable adhesion of the lens holder to the substrate.
Smart Images

Figure BDA0003642479120000161 
Figure HDA0003642479130000011 
Figure HDA0003642479130000012
Abstract
Description
Technical Field
[0001] The present invention relates to thermal and UV curable adhesive compositions. Background Art
[0002] A compact camera module equipped in a device such as a smartphone includes a lens, a cylindrical lens holder for holding the lens, and an image sensor fixed on a substrate and converting light collected by the lens into an electrical signal. In assembling such a compact camera module, the lens holder and the substrate on which the image sensor is fixed must be firmly adhered to each other, and they are adhered using a thermosetting adhesive (Patent Document 1).
[0003] When the lens holder is adhered to the substrate on which the image sensor is fixed, the distance between the lens and the image sensor must be accurately maintained. Specifically, the distance between the lens and the light receiving surface of the image sensor must match the focal distance of the lens. However, the use of such a heat-curing adhesive causes the distance between the lens and the image sensor to change during heat curing.
[0004] To solve this problem, Patent Document 2 proposes an adhesive that is cured by ultraviolet rays and heat. The use of such a heat and UV curable adhesive can accurately fix the distance between the lens and the image sensor by UV irradiation before the heat curing step that may cause positional shift.
[0005] Citation List
[0006] Patent Literature
[0007] Patent Document 1: JP2007-184801A
[0008] Patent Document 2: JP2017-101112A Summary of the invention
[0009] Technical issues
[0010] Materials with high coefficient of thermal expansion (CTE) such as polycarbonate are widely used as materials for lens holders. The present inventors have found that conventional heat and UV curable adhesives peel off or lose their heat resistance during thermal curing due to the large difference in CTE between the lens holder and the substrate.
[0011] An object of the present invention is to provide an adhesive which can resist peeling during thermal curing when adhering a lens holder to a substrate on which an image sensor is fixed when assembling a camera module; and which has excellent heat resistance after curing.
[0012] Solution to the problem
[0013] The present inventors have conducted extensive studies to achieve this object, and have found that this object is achieved by using a heat and UV curable adhesive composition comprising: (a) at least one urethane acrylate oligomer comprising at least one polycarbonate-based urethane acrylate oligomer, (b) at least one acrylate monomer, (c) at least one particle rubber, (d) at least one polyamine curing agent having a primary amine and / or a secondary amine, and (e) at least one photopolymerization initiator, wherein the at least one urethane acrylate oligomer (a) has a weight average molecular weight of 4,000 or more, and the at least one particle rubber (c) is present in an amount of 5% by weight or more in the entire composition. The present invention has been accomplished by further studies on this finding. The present invention includes the following embodiments.
[0014] Project 1.
[0015] A heat and UV curable adhesive composition comprising:
[0016] (a) at least one urethane acrylate oligomer comprising at least one polycarbonate-based urethane acrylate oligomer,
[0017] (b) at least one acrylate monomer,
[0018] (c) at least one kind of rubber particles,
[0019] (d) at least one polyamine curing agent having primary and / or secondary amines, and
[0020] (e) at least one photopolymerization initiator,
[0021] wherein the at least one polyurethane acrylate oligomer (a) has a weight average molecular weight of 4,000 or more, and
[0022] The at least one particulate rubber (c) is present in an amount of 5% by weight or more in the entire composition.
[0023] Project 2.
[0024] The heat and UV curable adhesive composition according to item 1, wherein the at least one urethane acrylate oligomer (a) comprises 50 wt % or more of the at least one polycarbonate-based urethane acrylate oligomer based on the total amount of the at least one urethane acrylate oligomer.
[0025] Project 3.
[0026] The heat and UV curable adhesive composition according to item 1 or 2, wherein the at least one particle rubber (c) is a core-shell type particle rubber.
[0027] Project 4.
[0028] The heat and UV curable adhesive composition according to any one of items 1 to 3, further comprising: (f) at least one chain transfer agent.
[0029] Item 5.
[0030] The heat and UV curable adhesive composition according to any one of items 1 to 4, further comprising: (g) at least one inorganic filler.
[0031] Item 6.
[0032] The heat and UV curable adhesive composition according to any one of items 1 to 5, which is used for assembling a camera module.
[0033] Item 7.
[0034] Use of a heat and UV curable adhesive composition in assembling a camera module, the heat and UV curable adhesive composition comprising:
[0035] (a) at least one urethane acrylate oligomer comprising at least one polycarbonate-based urethane acrylate oligomer,
[0036] (b) at least one acrylate monomer,
[0037] (c) at least one kind of rubber particles,
[0038] (d) at least one polyamine curing agent having primary and / or secondary amines, and
[0039] (e) at least one photopolymerization initiator,
[0040] wherein the at least one urethane acrylate oligomer (a) has a weight average molecular weight of 4,000 or more, and
[0041] The at least one particulate rubber (c) is present in an amount of 5% by weight or more in the entire composition.
[0042] Item 8.
[0043] A method of adhering a lens holder for a camera module to a camera module substrate having an image sensor fixed thereon,
[0044] The method comprises adhering the lens holder to the substrate by using a heat and UV curable adhesive composition,
[0045] wherein the heat and UV curable adhesive composition comprises:
[0046] (a) at least one urethane acrylate oligomer comprising at least one polycarbonate-based urethane acrylate oligomer,
[0047] (b) at least one acrylate monomer,
[0048] (c) at least one kind of rubber particles,
[0049] (d) at least one polyamine curing agent having primary and / or secondary amines, and
[0050] (e) at least one photopolymerization initiator,
[0051] wherein the at least one urethane acrylate oligomer (a) has a weight average molecular weight of 4,000 or more, and
[0052] The at least one particulate rubber (c) is present in an amount of 5% by weight or more in the entire composition.
[0053] Beneficial effects of the present invention
[0054] When assembling a camera module, using the heat and UV curable adhesive composition according to the present invention to adhere a lens holder to a substrate having an image sensor fixed thereon results in a reduced incidence of adhesive peeling during thermal curing and improved heat resistance after curing. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 is a graph showing an adhesion test performed in Examples.
[0056] Figure 2 is a diagram showing a peeling test performed in Examples. DETAILED DESCRIPTION
[0057] In this specification, the "weight average molecular weight" (M w ) refers to a value determined as a polystyrene equivalent value by gel permeation chromatography (GPC) using a solvent such as tetrahydrofuran as an eluent.
[0058] In the present specification, (meth)acrylate, (meth)acrylic acid, and (meth)acryloyl refer to acrylate or methacrylate; acrylic acid or methacrylic acid; and acryl or methacryloyl, respectively.
[0059] (a) Polyurethane acrylate oligomer
[0060] Polyurethane acrylate oligomers are well known to those skilled in the art. For example, polyurethane acrylate oligomers can be obtained by reacting a diisocyanate, preferably an aliphatic diisocyanate, with a hydroxy acrylate. Alternatively, polyurethane acrylate oligomers can be obtained, for example, by reacting a diisocyanate, preferably an aliphatic diisocyanate, a hydroxy acrylate, and a polyol.
[0061] At least one polyurethane acrylate oligomer (a) comprises at least one polycarbonate-based polyurethane acrylate oligomer. Polycarbonate-based polyurethane acrylate oligomers are well known to those skilled in the art. For example, polycarbonate-based polyurethane acrylate oligomers can be obtained by reacting diisocyanate (preferably aliphatic diisocyanate), hydroxy acrylate and polycarbonate.
[0062] The at least one polyurethane acrylate oligomer (a) contains preferably 50% by weight or more, more preferably 60% by weight or more, of at least one polycarbonate-based polyurethane acrylate oligomer based on the total amount of the at least one polyurethane acrylate oligomer. The at least one polyurethane acrylate oligomer used in the present invention may be composed of at least one polycarbonate-based polyurethane acrylate oligomer. Specific examples of the polycarbonate-based polyurethane acrylate oligomers used include UN9200A (Negami Chemical Industrial Co., Ltd.; weight average molecular weight of 15,000) and UV3310B (Mitsubishi Chemical Corporation; weight average molecular weight of 5,000).
[0063] At least one polyurethane acrylate oligomer (a) may also include at least one polyether-based polyurethane acrylate oligomer. Polyether-based polyurethane acrylate oligomers are well known to those skilled in the art. For example, polyether-based polyurethane acrylate oligomers can be obtained by reacting diisocyanates (preferably aliphatic diisocyanates), hydroxy acrylates, and polyethers. Specific examples of polyether-based polyurethane acrylate oligomers for use include UV6640B (Mitsubishi Chemical Corporation; weight average molecular weight of 5,000) and UN6202 (Negami Chemical Industrial Co., Ltd.; weight average molecular weight of 11,000).
[0064] The at least one urethane acrylate oligomer (a) has a weight average molecular weight of 4,000 or more.
[0065] From the viewpoint of ensuring excellent durability under thermal and mechanical stimulation and ensuring appropriate storage modulus by sufficiently forming a soft segment structure in the cured product, the weight average molecular weight of at least one urethane acrylate oligomer (a) is preferably 5,000 or more, more preferably 6,000 or more, still more preferably 8,000 or more, and still more preferably 10,000 or more. From the viewpoint of dispensability of the adhesive, the weight average molecular weight of at least one urethane acrylate oligomer (a) is preferably 20,000 or less, more preferably 18,000 or less, and still more preferably 16,000 or less.
[0066] From the viewpoint of elastic modulus control and adhesion after curing, the heat and UV curable adhesive composition according to the present invention contains at least one urethane acrylate oligomer (a) in a total amount of preferably 10 wt % or more, more preferably 15 wt % or more, based on the entire composition. From the viewpoint of elastic modulus control, dispensability and adhesion after curing, the heat and UV curable adhesive composition according to the present invention contains at least one urethane acrylate oligomer (a) in a total amount of preferably 40 wt % or less, more preferably 30 wt % or less, based on the entire composition.
[0067] From the viewpoint of elastic modulus and adhesiveness of the cured product, the glass transition temperature (Tg) of at least one urethane acrylate oligomer (a) is preferably 25° C. or lower. In particular, the glass transition temperature of the polycarbonate-based urethane acrylate oligomer is more preferably 10° C. or lower.
[0068] (b) Acrylate Monomer
[0069] The heat and UV curable adhesive composition according to the present invention further comprises at least one acrylate monomer (b). The at least one acrylate monomer (b) may be a monofunctional (meth)acrylate or a multifunctional (meth)acrylate.
[0070] Specific examples of the monofunctional methacrylate include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, glycidyl methacrylate, 2-hydroxyethyl methacrylate, 2-isocyanatoethyl methacrylate, isobornyl methacrylate (e.g., "IBXA", Osaka Organic Chemical Industry Ltd.), 2-methacryloxyethyltrimethoxysilane, 2-methacryloxyethyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxymethyldiethoxysilane, 4-methacryloxybutyltrimethoxysilane, 4-methacryloxybutyltriethoxysilane, dicyclopentenyloxyethyl methacrylate (e.g., FA-512M, produced by Hitachi Chemical Co., Ltd.), dicyclopentyl methacrylate (e.g., FA-513M, produced by Hitachi Chemical Co., Ltd.), pentamethylpiperidinyl methacrylate (e.g., FA-711MM, produced by Hitachi Chemical Co., Ltd.), tetramethylpiperidinyl methacrylate (e.g., FA-712HM, produced by Hitachi Chemical Co., Ltd.), methoxypolyethylene glycol methacrylate (e.g., produced by Hitachi Chemical Co., Ltd.), benzyl methacrylate (e.g., FA-BZM, produced by Hitachi Chemical Co., Ltd.), 2-hydroxy-3-acryloyloxypropyl methacrylate (e.g., Light Ester G-201P, produced by Kyoeisha Chemical Co., Ltd.), 2-methacryloyloxyethyl phthalate (e.g., CB-1, produced by Shin-Nakamura Chemical Co., Ltd.), methoxypolyethylene glycol methacrylate, phenoxyethylene glycol methacrylate (e.g., PHE-1G, produced by Shin-Nakamura Chemical Co., Ltd.), stearyl methacrylate (e.g., S, produced by Shin-Nakamura Chemical Co., Ltd.), 2-methacryloyloxyethyl succinate (e.g., SA, produced by Shin-Nakamura Chemical Co., Ltd.), and 3,4-epoxycyclohexylmethyl methacrylate (e.g., Cyclomer M100, produced by Daicel Corporation).
[0071] Specific examples of the bifunctional methacrylate include dipropylene glycol diacrylate (e.g., APG-100, Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol diacrylate (e.g., A-DCP, Shin-Nakamura Chemical Co., Ltd.), 1,4-butanediol dimethacrylate (e.g., FA-124M, produced by Hitachi Chemical Co., td.), neopentyl glycol dimethacrylate (e.g., FA-125M, produced by Hitachi Chemical Co., Ltd.), polyethylene glycol #200 dimethacrylate (e.g., FA-220M, produced by Hitachi Chemical Co., Ltd.), EO-modified bisphenol A dimethacrylate (e.g., FA-321M, produced by Hitachi Chemical Co., Ltd.), EO-modified polypropylene glycol #700 dimethacrylate (e.g., FA-023M, produced by Hitachi Chemical Co., Ltd.), ethylene glycol dimethacrylate (e.g., 1G, produced by Shin-Nakamura Chemical Co., Ltd.), diethylene glycol dimethacrylate (e.g., 2G, produced by Shin-Nakamura Chemical Co., Ltd.), triethylene glycol dimethacrylate (e.g., 3G, produced by Shin-Nakamura Chemical Co., Ltd.), polyethylene glycol dimethacrylate (e.g., produced by Shin-Nakamura Chemical Co., Ltd.), 2,2-bis[4-(methacryloyloxyethoxy)phenyl]propane (e.g., BPE-80N, produced by Shin-Nakamura Chemical Co., Ltd.), ethoxylated bisphenol A dimethacrylate (e.g., produced by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (e.g., DCP, produced by Shin-Nakamura Chemical Co., Ltd.), 1,10-decanediol dimethacrylate (e.g., DOD-N, produced by Shin-Nakamura Chemical Co., Ltd.), 1,6-hexanediol dimethacrylate (e.g., HD-N, produced by Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol dimethacrylate (e.g., NOD-N, produced by Shin-Nakamura Chemical Co., Ltd., neopentyl glycol dimethacrylate (e.g., NPG, produced by Shin-Nakamura Chemical Co., Ltd.), ethoxylated polypropylene glycol dimethacrylate (e.g., produced by Shin-Nakamura Chemical Co., Ltd.), glycerol dimethacrylate (e.g., 701, produced by Shin-Nakamura Chemical Co., Ltd.), and polypropylene glycol dimethacrylate (e.g., produced by Shin-Nakamura Chemical Co., Ltd.). .
[0072] Specific examples of the polyfunctional (trifunctional or higher) methacrylate include trimethylolpropane trimethacrylate (eg, TMPT, produced by Shin-Nakamura Chemical Co., Ltd.).
[0073] The heat and UV curable adhesive composition according to the present invention may include only one acrylate monomer (b) or two or more acrylate monomers (b).
[0074] From the viewpoint of excellent UV curability and crosslink density control, the heat and UV curable adhesive composition according to the present invention contains at least one acrylate monomer (b) in a total amount of preferably 10 wt% or more, more preferably 15 wt% or more, based on the entire composition. From the viewpoint of elastic modulus control after curing, dispensability and adhesion, the heat and UV curable adhesive composition according to the present invention contains at least one urethane acrylate oligomer (a) in a total amount of preferably 40 wt% or less, more preferably 30 wt% or less, based on the entire composition.
[0075] (c) Crumb rubber
[0076] At least one particulate rubber (c) is added to eliminate the mismatch in thermal expansion coefficients between the substrate surface and the adhesive. This can prevent, for example, peeling or cracking of the adhesive due to heat and / or physical shock.
[0077] At least one rubber particle (c) is preferably a core-shell type rubber particle. The material of the rubber particle can be any material. For example, widely used styrene-butadiene rubber can be used for the core part.
[0078] The heat- and UV-curable adhesive composition according to the present invention may contain only one kind of particle rubber (c) or two or more kinds of particle rubber (c).
[0079] From the viewpoint of eliminating the mismatch in thermal expansion coefficient between the substrate surface and the adhesive, the heat and UV curable adhesive composition according to the present invention contains preferably 3 wt % or more, more preferably 4 wt % or more of at least one particulate rubber (c), based on the entire composition. The heat and UV curable adhesive composition according to the present invention contains preferably 20 wt % or less, more preferably 15 wt % or less, still more preferably 10 wt % or less of at least one particulate rubber (c), based on the entire composition.
[0080] (d) Polyamine curing agents with primary and / or secondary amines
[0081] The at least one polyamine curing agent (d) is a polyamine-based thermal curing agent having primary and / or secondary amines.
[0082] From the viewpoint of extending the life of the product, the melting point of the at least one polyamine curing agent (d) is preferably 50° C. or higher, more preferably 60° C. or higher. From the viewpoint of having sufficient thermosetting property at a normal thermosetting temperature (generally 80° C.), the melting point of the at least one polyamine curing agent (d) is 80° C. or lower, more preferably 70° C. or lower.
[0083] Specific examples of the polyamine-based thermal curing agent having primary and / or secondary amines include Fujicure FXR-1020, FXR-1030, FXR-1050, and FXR-1080 (all produced by Fuji Kasei Kogyo KK); and Adeka hardeners EH-4357S, EH-5030S, EH-5057PK, and EH-5057PK (all produced by ADEKA Corporation).
[0084] The heat and UV curable adhesive composition according to the present invention may contain one polyamine curing agent (d) or two or more polyamine curing agents (d).
[0085] From the viewpoint of excellent adhesion and sufficient addition reaction between the acrylate monomer and the oligomer, the heat and UV curable adhesive composition according to the present invention contains preferably 10 wt % or more, more preferably 20 wt % or more of at least one polyamine curing agent (d) based on the entire composition. From the viewpoint of excellent moisture resistance and dispensability, the heat and UV curable adhesive composition according to the present invention contains preferably 40 wt % or less, more preferably 30 wt % or less of at least one polyamine curing agent (d) based on the entire composition.
[0086] (e) Photopolymerization initiator
[0087] The at least one photopolymerization initiator (e) may be any photopolymerization initiator, and the at least one photopolymerization initiator (e) for use may be those commonly used in the art.
[0088] Specific examples of the photopolymerization initiator (e) include IRGACURE 651 (2,2-dimethoxy-1,2-diphenylethan-1-one), IRGACURE 184 (1-hydroxy-cyclohexyl-phenyl-ketone), DAROCUR 1173 (2-hydroxy-2-methyl-1-phenyl-propan-1-one), IRGACURE 2959 (1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one), IRGACURE 127 (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one), IRGACURE 907 (2-methyl-1-(4-methylphenylthio)-2-morpholinopropan-1-one), IRGACURE IRGACURE 369 (2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone), IRGACURE 379 (2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone), DAROCUR TPO (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide), IRGACURE 819 (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide), IRGACURE 784 (bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium), IRGACURE OXE 01 (1,2-octanedione, 1-[4-(phenylthio)-, 2-(o-benzoyl oxime)]), IRGACURE OXE 02 (ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetoxime)), IRGACURE 754 (a mixture of 2-[2-oxo-2-phenylacetoxyethoxy]ethyl oxyphenylacetate and 2-(2-hydroxyethoxy)ethyl oxyphenylacetate), Lucirin TPO, LR8893 and LR8970 (all of which are produced by BASF Japan Ltd.); DETX-S (2,4-diethylthioxanthone) (produced by Nippon Kayaku Co., Ltd.); and Ebecryl P36 (produced by UCB).
[0089] The at least one photopolymerization initiator (e) for use may be one photopolymerization initiator (e) or a combination of two or more photopolymerization initiators (e).
[0090] From the viewpoint of excellent UV curability, the heat and UV curable adhesive composition according to the present invention contains preferably 0.5 wt % or more, more preferably 1 wt % or more of at least one photopolymerization initiator (e) based on the entire composition. From the viewpoint of stability of adhesiveness, the heat and UV curable adhesive composition according to the present invention contains preferably 5 wt % or less, more preferably 2 wt % or less of at least one photopolymerization initiator (e) based on the entire composition.
[0091] (f) Chain transfer agent
[0092] The thermally and UV-curable adhesive composition according to the invention may also comprise at least one chain transfer agent (f).
[0093] The chain transfer agent has the function of transferring the activity of the growing polymer chain to another molecule in the polymerization reaction. The effect of the chain transfer agent in the polymerization reaction proportionally reduces the amount of relatively long molecular chains and the amount of relatively short molecular chains, thereby narrowing the molecular weight distribution. This reduces the number of molecules with higher molecular weights, thereby giving the composition obtained in the polymerization reaction a desired hardness.
[0094] At least one chain transfer agent (f) is preferably a mercaptan. Specific examples of the chain transfer agent (f) being a mercaptan include n-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, methyl mercaptan, ethyl mercaptan, tert-butyl mercaptan, benzyl mercaptan, tert-nonyl mercaptan, thioglycolic acid, isooctyl thioglycolate, 2-ethylhexyl thioglycolate, 1,8-dimercapto-3,5-dioxaoctane, dibenzyl thiocarbonate, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3 -mercaptopropionate, methoxybutyl-3-mercaptopropionate, stearyl-3-mercaptopropionate, 1,8-dimercapto-3,6-dioxaoctane, trimethylolpropane tris-3-mercaptopropionate, tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, pentaerythritol tetrakis-3-mercaptopropionate, pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate) and dipentaerythritol hexa-3-mercaptopropionate.
[0095] The at least one chain transfer agent (f) for use may be one chain transfer agent (f) or a combination of two or more chain transfer agents (f).
[0096] From the viewpoint of imparting a higher hardness (i.e., sufficient toughness) to the cured product and / or reducing the unevenness in the cured product, the heat and UV curable adhesive composition according to the present invention comprises 5 wt % or more, more preferably 10 wt % or more of at least one chain transfer agent (f) based on the entire composition. From the viewpoint of imparting an appropriate hardness (i.e., sufficient film tensile strength) to the cured product, the heat and UV curable adhesive composition according to the present invention comprises 20 wt % or less, more preferably 15 wt % or less of at least one chain transfer agent (f) based on the entire composition.
[0097] (g) Inorganic fillers
[0098] The heat and UV curing adhesive composition according to the invention may also comprise at least one inorganic filler (g).The addition of at least one inorganic filler (g) enables the properties of the heat and UV curing adhesive composition to be controlled, such as the thermal expansion coefficient and the rheology.
[0099] The at least one inorganic filler (g) includes silica fillers such as colloidal silica, hydrophobic silica, fine silica and nano silica; acrylic beads; glass beads; polyurethane beads; bentonite; acetylene black; and Ketjenblack.
[0100] The average particle size of at least one inorganic filler (g) (the maximum average size if the filler is not in the form of particles) can be any size, and is preferably 0.01 μm or more from the perspective of excellent handling of the heat and UV curable adhesive composition. From the perspective of uniform dispersion of the filler in the heat and UV curable adhesive composition, the average particle size of at least one inorganic filler (g) (the maximum average size if the filler is not in the form of particles) is preferably 50 μm or less. In the present invention, the average particle size of the inorganic filler refers to the value measured by a dynamic light scattering Nanotrac particle size analyzer.
[0101] Specific examples of the inorganic filler (g) include synthetic high-purity spherical silica SO-E5 or SO-E2 (produced by Admatechs Company Limited, average particle size of SO-E5: 2 μm, average particle size of SO-E2: 0.6 μm), silica FB7SDX (produced by Tatsumori Ltd., average particle size: 10 μm) and silica TS-10-034P (produced by Micron, average particle size: 20 μm).
[0102] The at least one inorganic filler (g) for use may be one inorganic filler (g) or a combination of two or more inorganic fillers (g).
[0103] From the viewpoint of adhesive shrinkage and thermal expansion control, the heat and UV curable adhesive composition according to the present invention contains preferably 0.5 wt % or more, more preferably 1 wt % or more of at least one inorganic filler (g) based on the entire composition. From the viewpoint of elastic modulus and initial adhesion, the heat and UV curable adhesive composition according to the present invention contains preferably 20 wt % or less, more preferably 10 wt % or less of at least one inorganic filler (g) based on the entire composition.
[0104] (h) Other components
[0105] The heat and UV curable adhesive composition according to the present invention may further comprise other components, including various coupling agents as adhesion promoters, such as silanes and titanates, and rheology modifiers, such as fumed silica.
[0106] Physical properties
[0107] The storage modulus (25° C.) of the heat and UV curable adhesive composition according to the present invention after curing by heat and UV is preferably 800 MPa or less, more preferably 500 MPa or less. The storage modulus (25° C.) within these ranges after curing by heat and UV makes it unlikely that a mismatch in thermal expansion coefficient will occur between the substrate surface and the adhesive, even due to heat and / or physical shock.
[0108] use
[0109] The heat and UV curable adhesive composition according to the present invention is preferably used for assembling a camera module. More specifically, the heat and UV curable adhesive composition according to the present invention is preferably used for assembling a camera module to adhere a lens holder to a substrate on which an image sensor is fixed. The camera module may be any camera module; for example, a compact camera module for a smartphone or other such device.
[0110] Example
[0111] Hereinafter, the present invention will be described with reference to Examples. However, the present invention is not limited to these Examples. Unless a unit is specified, the value of each component in the table represents weight (g).
[0112] The adhesive compositions of Comparative Examples 1 to 4 and Examples 1 to 3 were prepared by mixing the components in the composition ratios shown in Table 1. More specifically, a three-roll mill was used to well disperse an acrylate monomer in which a heat curing agent, particulate rubber, a photopolymerization initiator, an inorganic filler, and a chain transfer agent were dissolved, and one or more urethane acrylate oligomers. The obtained mixture and other additives were mixed with a planetary mixer, and further vacuum degassed to obtain an adhesive composition.
[0113] The physical properties were evaluated as follows. Table 1 shows the evaluation results.
[0114] Storage modulus test
[0115] The prepared adhesive slurries were each cured to a thickness of 1 mm under the following conditions: at 500 mW / cm 2 4 seconds at 100°C and 60 minutes at 80°C; thereby forming a sheet. Each sheet was cut into strips (width: 10 mm) and subjected to dynamic mechanical analysis (DMA) in a tensile mode to measure the storage modulus E' at temperatures ranging from -40°C to 250°C.
[0116] Adhesion test
[0117] Figure 1 The process is shown. The details are as follows. About 3.5 mg of each adhesive composition (by weight) was distributed on a ceramic substrate (15 mm × 15 mm) to form a hollow square (5 mm × 5 mm). Then, a PC chip (7 mm × 7 mm) was mounted thereon, and the thickness of the adhesive was adjusted to 100 μm. Irradiation was performed from four circumferential directions with a 365-nm LED (500 mW / cm 2 The samples were then cured by heating at 80°C for 60 minutes in a hot air circulation oven and measured with a 4000 Optima adhesion tester (produced by Dage) at a shear rate of 200 μm / s and a shear height of 120 μm.
[0118] Peel test
[0119] The adhesion test was performed at 80° C. for 60 minutes until the adhesive was thermally cured. After the temperature cycle test, the adhesive was checked by SEM to see if it peeled off.
[0120] The temperature and humidity test was conducted at 85° C. and 85% RH (relative humidity) for 250 hours.
[0121] The temperature cycling test was performed at -40 to 85°C for 250 cycles.
[0122] Example 1
[0123] The heat and UV curable adhesive composition of Example 1 comprises a w ) is 5,000 and a polyether-based polyurethane acrylate oligomer having a Tg of -27°C and a weight average molecular weight (M w) is 15,000 as the urethane acrylate oligomer.
[0124] Table 1 shows the evaluation results. The results show that curing of the heat and UV curable adhesive composition of Example 1 by UV irradiation is easy due to the presence of the acrylate monomer. Since the cured product has low elasticity and contains an appropriate amount of particulate rubber, it is naturally expected that the cured product has durability under physical impact; in addition, the evaluation results show that the cured product also has durability under heating. In addition, the results show that the cured product has excellent initial adhesion during thermal curing and has excellent durability due to the presence of a polyamine curing agent having a primary or secondary amine.
[0125] Comparative Example 1
[0126] The heat and UV curable adhesive composition of Comparative Example 1, which included only a polyether-based urethane acrylate oligomer as the urethane acrylate oligomer, was not excellent in adhesion and durability, and peeled off after the temperature cycle test.
[0127] Example 2
[0128] The heat and UV curable adhesive composition of Example 2 only comprises w ) is 15,000 as the urethane acrylate oligomer.
[0129] Table 1 shows the evaluation results. The results show that the heat and UV curable adhesive composition of Example 2 is easily cured by UV irradiation due to the presence of the acrylate monomer. Because the cured product contains an appropriate amount of particulate rubber, the cured product is durable under heat and physical shock. In addition, the results show that the cured product has excellent initial adhesion during thermal curing and has excellent durability due to the presence of a polyamine curing agent having a primary or secondary amine.
[0130] Comparative Example 2
[0131] Because the heat and UV curable adhesive composition of Comparative Example 2 does not contain a sufficient amount of particulate rubber, the cured product does not have excellent durability under heat and physical shock and exhibits an excessively high storage modulus. These results also lead to peeling after the temperature cycle test.
[0132] Example 3
[0133] The heat and UV curable adhesive composition of Example 3 comprises a Tg of 12° C. and a weight average molecular weight (M w ) is 5,000 and a polyether-based polyurethane acrylate oligomer having a Tg of -27°C and a weight average molecular weight (Mw ) is 15,000 as the urethane acrylate oligomer.
[0134] Table 1 shows the evaluation results. The results show that curing of the heat and UV curable adhesive composition of Example 3 by UV irradiation is easy due to the presence of the acrylate monomer. Because the cured product contains an appropriate amount of particulate rubber, the cured product is durable under heat and physical impact. In addition, the results show that the cured product has excellent initial adhesion during thermal curing and has excellent durability due to the presence of a polyamine curing agent having a primary or secondary amine.
[0135] Comparative Example 3
[0136] Although the heat and UV curable adhesive composition of Comparative Example 3 contains polycarbonate-based urethane acrylate oligomer and polyether-based urethane acrylate oligomer as urethane acrylate oligomers, the cured product is not good in durability under heat and physical impact, and exhibits too high storage modulus because it fails to form a sufficient soft segment structure due to its weight average molecular weight of about 3,000. These results also lead to peeling after the temperature cycle test.
[0137] Comparative Example 4
[0138] The heat and UV curable adhesive composition of Comparative Example 4 exhibited insufficient heat curing due to the presence of an imidazole-based heat curing agent as a heat curing agent in the adhesive composition.
[0139]
Claims
1. A heat and UV curable adhesive composition comprising: (a) at least one urethane acrylate oligomer comprising at least one polycarbonate-based urethane acrylate oligomer, (b) at least one acrylate monomer, (c) at least one kind of rubber particles, (d) at least one polyamine curing agent having primary and / or secondary amines, and (e) at least one photopolymerization initiator, wherein the at least one urethane acrylate oligomer (a) has a weight average molecular weight of 5,000 or more and 18,000 or less, and The at least one polyurethane acrylate oligomer (a) is present in the entire composition in an amount of 10 wt % or more and 40 wt % or less, The at least one acrylate monomer (b) is present in the entire composition in an amount of 10 wt % or more, The at least one particulate rubber (c) is present in the entire composition in an amount of 5% by weight or more, The at least one polyamine curing agent (d) is present in an amount of 10 wt % or more and 40 wt % or less in the entire composition, and, The at least one photopolymerization initiator (e) is present in an amount of 0.5 wt % or more and 5 wt % or less in the entire composition.
2. The heat and UV curable adhesive composition according to claim 1, wherein the at least one urethane acrylate oligomer (a) comprises 50 wt% or more of the at least one polycarbonate-based urethane acrylate oligomer based on the total amount of the at least one urethane acrylate oligomer.
3. The heat and UV curable adhesive composition according to claim 1 or 2, wherein the at least one particle rubber (c) is a core-shell type particle rubber.
4. The heat and UV curable adhesive composition according to claim 1 or 2, further comprising: (f) at least one chain transfer agent.
5. The heat and UV curable adhesive composition according to claim 1 or 2, further comprising: (g) at least one inorganic filler.
6. The heat and UV curable adhesive composition according to claim 1 or 2, which is used for assembling a camera module.
7. Use of a heat and UV curable adhesive composition in assembling a camera module, the heat and UV curable adhesive composition comprising: (a) at least one urethane acrylate oligomer comprising at least one polycarbonate-based urethane acrylate oligomer, (b) at least one acrylate monomer, (c) at least one kind of rubber particles, (d) at least one polyamine curing agent having primary and / or secondary amines, and (e) at least one photopolymerization initiator, wherein the at least one urethane acrylate oligomer (a) has a weight average molecular weight of 5,000 or more and 18,000 or less, and The at least one polyurethane acrylate oligomer (a) is present in the entire composition in an amount of 10 wt % or more and 40 wt % or less, The at least one acrylate monomer (b) is present in the entire composition in an amount of 10 wt % or more, The at least one particulate rubber (c) is present in the entire composition in an amount of 5% by weight or more, The at least one polyamine curing agent (d) is present in an amount of 10 wt % or more and 40 wt % or less in the entire composition, and, The at least one photopolymerization initiator (e) is present in an amount of 0.5 wt % or more and 5 wt % or less in the entire composition.
8. A method of adhering a lens holder for a camera module to a camera module substrate having an image sensor fixed thereon, the method comprising adhering the lens holder to the substrate by using a heat and UV curable adhesive composition, wherein the heat and UV curable adhesive composition comprises: (a) at least one urethane acrylate oligomer comprising at least one polycarbonate-based urethane acrylate oligomer, (b) at least one acrylate monomer, (c) at least one kind of rubber particles, (d) at least one polyamine curing agent having primary and / or secondary amines, and (e) at least one photopolymerization initiator, wherein the at least one urethane acrylate oligomer (a) has a weight average molecular weight of 5,000 or more and 18,000 or less, and The at least one polyurethane acrylate oligomer (a) is present in the entire composition in an amount of 10 wt % or more and 40 wt % or less, The at least one acrylate monomer (b) is present in the entire composition in an amount of 10 wt % or more, The at least one particulate rubber (c) is present in the entire composition in an amount of 5% by weight or more, The at least one polyamine curing agent (d) is present in an amount of 10 wt % or more and 40 wt % or less in the entire composition, and, The at least one photopolymerization initiator (e) is present in an amount of 0.5 wt % or more and 5 wt % or less in the entire composition.
Citation Information
Patent Citations
Photocurable and thermosetting resin composition
JP2017101112A
Insulating sheet and multilayer structure
CN101796106A
Thermally and actinically curable adhesive composition
CN101939391A
Thermosetting resin composition and copper foil-clad laminated sheet prepared by using thermosetting resin composition
CN102850727A
Photocurable sheet-type adhesive composition for optical use
CN104169388A